The information professional as an eCommerce manager - Serrano-Cobos, Jorge (Anuario ThinkEPI, 2014)
Spain is among the countries where online sales are growing fastest, with well over 2,000 activeo nline stores. However, there are not yet many trained and experienced eCommerce professionals, which presents an opportunity for those with knowledge of Information Management to colonize an immature labour niche. The article describes some of the "skills" that eCommerce managers need today, and howthisfits the profile of the Information Management graduate curriculum. Related skills include classifying and describing products, diagnosing search engine optimization problems, designing SEO strategy, coordinating internal and external communities of users, managing suppliers, conducting online market researchthrough competitive intelligence, studying the usability of the website and design / redesigning the interaction of the same, analyzing user interactions with web analytics tools, or even managing digital advertising.